Expansion of forest cover and coeval shifts in Later Stone Age land-use at Taforalt and Rhafas Caves, Morocco, as inferred from carbon isotopes in ungulate tooth enamel - Kayla B. Worthey; Philippe Fernandez; Elaine Turner; Teresa E. Steele; Louise Humphrey; R. Nick E. Barton; Jean-Jacques Hublin; Abdeljalil Bouzouggar (PLoS ONE, 2025)
Later Stone Age (Iberomaurusian) hunter-gatherer groups in northwestern Africa appear to have experienced a major reorganization of land-use strategies and settlement dynamics around 15–13 cal ka BP, which broadly corresponds to the globally recognized Greenland Interstadial 1 (Bølling-Allerød) climate interval. However, our understanding of the local impacts of this interval on environments in Morocco is incomplete, as is our understanding of the strength of the relationship, if any, between paleoenvironmental change and human behavior in the Moroccan Later Stone Age. This paper reconstructs changes through time in local forest canopy cover during the Later Stone Age around the archaeological cave sites of Taforalt and Rhafas (northeastern Morocco), using stable isotopes of carbon in ungulate tooth enamel. Results indicate a close link between tree cover expansion during Greenland Interstadial 1 and changes in land-use behaviors, which at Taforalt included the exploitation of storable oak and pine-derived plant foods and greater intensity of site occupation. High local productivity of nut-bearing trees paired with regional increases in human population densities likely contributed to greater intensity of occupations at Taforalt and Rhafas during Greenland Interstadial 1.